Building Solar Capacity in Maine: The Greater Bangor Solarize Case Study - Stone, Thomas; Klein, Sharon; McKeage, Kim (Maine Policy Review, 2021)
Despite being a mature technology with significantly decreasing costs over the last decade and various financial incentives available periodically, solar photovoltaic energy systems currently generate approximately 1 percent of Maine’s electricity. There have been eight Solarize campaigns in Maine, which aimed to increase residential- and commercial-scale solar adoption through group purchasing. In 2017, the Greater Bangor Solarize campaign increased the number of residential solar installations by 63 percent and solar power capacity by 52 percent in the participating towns compared to the previous seven years. We surveyed the Greater Bangor Solarize participants to better understand the motivations, concerns, and barriers to residential solar adoption in central Maine. We find a significant demographic divide exists between the Solarize participants and the general Maine population. We also observe that environmental stewardship and energy security are the primary motivations for considering solar and that overall cost remains the primary concern.
Keywords: community solar; motivations for solar; solar adoption; residential solar electric